Effects of Spatial Location of Auditory Tones on Pitch Discrimination. Issue 2 (April 2020) - Flagge, Ashley G.; Estis, Julie M.; Moore, Robert E.
Pitch discrimination accuracy has been found to be affected by many factors, including handedness, musical training, interfering stimuli, and spatial location of the auditory stimulus. Separating the stimulus input location of interference tones from initial (reference) and final (comparison) tones leads to more accurate pitch discrimination, but the effects of spatial location relationships between the reference, interference, and comparison tones have not been fully explored. This study examined the impact of stimulus spatial location in 24 young, nonmusician females. Participants determined whether the pitch of reference and comparison tones were the same or different in 20 pitch discrimination conditions with varied interference, spatial relationships, and frequencies. Findings revealed that pitch discrimination accuracy was significantly better when (a) there was no interference, (b) the comparison tone was presented to the contralateral brain hemisphere from reference and interference tones, and (c) the comparison tone was presented to the left ear. We discussed the implications of these findings for therapy programs to strengthen pitch discrimination abilities.